Correlation of Plasma EGF with Striatal Dopamine Transporter Availability in Healthy Subjects. Issue 1 (December 2017) - Pak, Kyoungjune; Shin, Seunghyeon; Kim, So; Kim, Keunyoung; Kim, Bum; Kim, Seong; Kim, In
Abstract We aimed to evaluate the association between plasma epidermal growth factor (EGF) and the availability of dopamine transporter (DAT) measured from123 I-FP-CIT single-photon emission computed tomography in healthy controls in this study. Volume of interest template was applied to measure specific binding ratios (SBRs) of caudate nucleus, putamen, and striatum representing DAT availability as follows; SBR = (target– cerebellum)/cerebellum. Plasma EGF was negatively correlated with the availabilities of both caudate nucleus (r = −0.261, p = 0.019), and putamen (r = −0.341, p = 0.002). After dividing subjects according to Apo E genotyping, DAT availability of caudate nucleus of Apo e4 non-carriers (n = 60) showed the positive correlation with cerebrospinal fluid (CSF) α-synuclein (r = 0.264, p = 0.042). Plasma EGF was negatively correlated with DAT availabilities of Apo e4 non-carriers. Further studies are needed to clarify underlying mechanisms of this phenomenon.